Determinan Cash Holding Sebelum Dan Selama Pandemi COVID-19 - Yanti; Liana Susanto; Timothy Brian Kurniawan (Jurnal Ekonomi, 2023)
This study aims to analyze the effect of institutional ownership, board size, capital expenditure, net working capital, liquidity, leverage, cash flow ratio on cash holding before and during the COVID-19 pandemic, and differences in average cash holding. Based on purposive sampling, there are 85 manufacturing companies during 2019-2020. Hypothesis testing with regression analysis and Wilcoxon signed-rank test using SPSS. Research before the pandemic shows board size, leverage, and cash flow ratio have a significant effect on cash holding, Research during the pandemic shows that capital expenditure, liquidity, leverage, and cash flow ratio have a significant effect on cash holding. Study finds significant differences between average cash holding before and during the pandemic.